2011
DOI: 10.1094/pdis-04-11-0278
|View full text |Cite
|
Sign up to set email alerts
|

Mowing Frequency and Plant Growth Regulator Effects on Dollar Spot Severity and on Duration of Dollar Spot Control by Fungicides

Abstract: Putman, A. I., and Kaminski, J. E. 2011. Mowing frequency and plant growth regulator effects on dollar spot severity and on duration of dollar spot control hy fungicides. Plant Dis. 95:1433-1442.Management of dollar spot (incited by Sclerotinia homoeocarpa) on golf course fairways is increasingly challenging. The objectives of this study were to determine the influence of mowing frequency and plant growth regulators (PGRs) on dollar spot severity and on the residual efficacy of fungicides for control of dollar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Mowing practices and dew removal strategies associated with fungicide performance for dollar spot control in creeping bentgrass (Agrostis stolonifera L.) have been evaluated recently. Putman and Kaminski (2011) found that mowing frequency (e.g., 2, 4, or 6 d/ week) had no influence on fungicide performance. In another study, Delvalle et al (2011) reported that dollar spot control with fungicides can be extended by daily dew removal or increased mowing frequency.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…Mowing practices and dew removal strategies associated with fungicide performance for dollar spot control in creeping bentgrass (Agrostis stolonifera L.) have been evaluated recently. Putman and Kaminski (2011) found that mowing frequency (e.g., 2, 4, or 6 d/ week) had no influence on fungicide performance. In another study, Delvalle et al (2011) reported that dollar spot control with fungicides can be extended by daily dew removal or increased mowing frequency.…”
mentioning
confidence: 88%
“…Burpee et al (1996) found that when TE was applied alone, it had no significant effect on dollar spot, but when applied in combination with chlorothalonil, iprodione, and propiconazole, it enhanced fungicide efficacy in 1 year of the 2-year study. Putman and Kaminski (2011) reported TE had no influence on dollar spot when applied in combination with fungicides. In the absence of fungicides, however, TE has been shown to significantly suppress dollar spot (Golembiewski and Danneberger, 1998;Putman and Kaminski, 2011).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…However, Lee et al (2003) reported that none of 12 tested biostimulants (some of them containing microbe extracts) reduced dollar spot in creeping bentgrass when compared with nitrogen applications. Despite the above‐mentioned cultural and biological dollar spot control strategies, the use of fungicides is generally required to maintain acceptable turf quality on golf courses (Putman and Kaminski, 2011), and fungicides have been the most successful tool for managing dollar spot (Walsh et al, 1999). In the United States, greenkeepers frequently apply two or more fungicide products with different modes of action repeated over a 14‐ to 28‐d interval for dollar spot control (Fidanza et al, 2006).…”
mentioning
confidence: 99%